ANALISIS PENGARUH INFLASI DAN PDRB TERHADAP JUMLAH PERMINTAAN KREDIT PADA PT. PEGADAIAN KOTA PONTIANAK - B01107100, SRI YULIANI (Jurnal Pembangunan dan Pemerataan, 2013)
This study entitled Analysis of Effect of Inflation and PDRB Against Credit On Demand PT. Pegadaian Pontianak, aims to identify and analyze the effect of inflation (X1) and PDRB (X2) on the demand for credit at PT. Pegadaian Pontianak City and to determine which variables are most influential. In this study, the data used are time series data. Forms of research that the authors use is descriptive research method, the multiple linear regression models. Based on the results of research conducted by the authors to conclude that inflation (X1) and GDP (X2) has a positive on the demand for credit at PT. Pegadaian Pontianak. The coefficient of determination (R2) showed a strong relationship between the independent variables (inflation and PDRB) on the dependent variable (loan request). Concurrent test results (Test f) shows that the simultaneous inflation (X1) and PDRB (X2) a significant effect on the demand for credit at PT. Pegadaian Pontianak. Partially (t test) variable greatest influence on the demand for credit at PT. Pegadaian Pontianak City is the PDRB variable (X2). Based on the results of this study concluded that people do pawn loans intended to finance their needs. when the income the greater the amount of spending would encourage consumption, and increase the confidence of the public to be able to repay loans. While inflation in which prices of goods increase, resulting in declining purchasing power. Finally, the general public still do pawn loans to finance his life. Keywords: Inflation, PDRB, Credit